Calidad de vida individual en niños y adolescentes con discapacidad intelectual y múltiple: una propuesta de atención basada en el modelo de Schalock y verdugo (2021)
Because to the significant increase in the number of research that seeks to characterize and enhance the quality of life of the population with disabilities at different times in their trajectory of life, if had been evidence of the difficulties of progress around the study of the life of children and adolescents in this condition, specifically, those with intellectual and multiple disabilities. The aim of this study was to analyze the construct of individual quality of life in children and adolescents with intellectual and multiple disabilities, based on a review of the theoretical and empirical antecedents carried out according to the postulates of the model proposed by Schalock and Verdugo, as a framework of reference for the development of research and attention strategies aimed at promoting as a final goal, a state full of well-being for these children and adolescents within the Colombian context. Some practical reflections were formulated, based on a case, to account for the attention evidence-based processes that effectively responded to the needs of children and adolescents with intellectual and multiple disabilities, their families and Institutions and organizations. Finally, the Schalock and Verdugo model has established itself as conceptual and methodological framework, updated and with great potential for change for children and adolescents of this group, because it has a scope and an impact capacity that allows it to timely attend from the onto to the macrosystem.